If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -4) = 2x + -6 Reorder the terms: 3(-4 + x) = 2x + -6 (-4 * 3 + x * 3) = 2x + -6 (-12 + 3x) = 2x + -6 Reorder the terms: -12 + 3x = -6 + 2x Solving -12 + 3x = -6 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -12 + 3x + -2x = -6 + 2x + -2x Combine like terms: 3x + -2x = 1x -12 + 1x = -6 + 2x + -2x Combine like terms: 2x + -2x = 0 -12 + 1x = -6 + 0 -12 + 1x = -6 Add '12' to each side of the equation. -12 + 12 + 1x = -6 + 12 Combine like terms: -12 + 12 = 0 0 + 1x = -6 + 12 1x = -6 + 12 Combine like terms: -6 + 12 = 6 1x = 6 Divide each side by '1'. x = 6 Simplifying x = 6
| 12x(x-9)=0 | | 2(2x-3)=3(x-10) | | -5X+12=5X^2-12 | | N^3+n^2-6n=0 | | 14-7x=43-14x | | 2n^2+12n+15=-3 | | 2n^2+12n+15=3 | | 2n^2+n-120=0 | | 10x^2n+47xny+42y^2n=0 | | 5g+15=2g | | -4x^3-2x+1=0 | | 6x+38=14 | | 27u^2+54uv-21v^2=0 | | 1x-2y-3z=0 | | Y^2+4Y+11=0 | | (2x-3)(x^2-5x+3)=0 | | -8-3c=19 | | ln^2x+lnx=12 | | 10x^2-21x+2=0 | | 4x-12=-30 | | 144x^2-96x-84=0 | | s^2d^2+9sd+14= | | 2-ln(3-x)=0 | | 9x^2y^2-12x^2y^2-3x^2y^2= | | a^3+1000b^3=0 | | 3e^3=10 | | 4x^2-72x+299=0 | | 20x+30(100-x)=2350 | | 4(x)=215 | | x^3+14x^2=-49x | | x^3+14x^2=-49 | | -3x^2-16x+35= |